The species group Amabilis of the genus Euplocania Enderlein (Psocodea: Psocomorpha: Ptiloneuridae) - Vinasco-Mondragón, Andrés Felipe; González-Obando, Ranulfo; García-Aldrete, Alfonso N. (Zootaxa, 2018)
We here describe and illustrate 11 species of Euplocania in species group Amabilis from Brazil, Colombia and Ecuador. They raise to 33 the number of species described in the genus. An identification key to the males in the species group is included.